2017
DOI: 10.12968/bjon.2017.26.3.172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of work environment on patient and nurse outcomes

Abstract: A good work environment constitutes a determinant factor for high care quality and, at the same time, relates to improved outcomes for the nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
148
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(162 citation statements)
references
References 31 publications
2
148
0
12
Order By: Relevance
“…Researchers have suggested that good work environment could positively influence nurses' job satisfaction (Aiken et al, 2011;Copanitsanou, Fotos, & Brokalaki, 2017). According to Lake (2002), work environment refers to the organizational characteristics of a work setting that facilitates or constrains professional nursing practice.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested that good work environment could positively influence nurses' job satisfaction (Aiken et al, 2011;Copanitsanou, Fotos, & Brokalaki, 2017). According to Lake (2002), work environment refers to the organizational characteristics of a work setting that facilitates or constrains professional nursing practice.…”
Section: Introductionmentioning
confidence: 99%
“…Condiciones del ambiente hospitalario y las características de la funciones de enfermería han hecho que esta sea catalogada como una profesión de riesgo y mayor prevalencia para el desarrollo del síndrome de Burnout (5,(17)(18)(19) . En Colombia se han desarrollado investigaciones (en ciudades especificas), que se han orientado a describir la prevalencia del síndrome o sus factores asociados, se han realizado principalmente en docentes (20,21) y en profesionales de la salud (14,15,(22)(23)(24)(25) .…”
Section: Discussionunclassified
“…El comportamiento de las variables sociodemográficas y laborales es similar a lo descrito por otros autores; en el presente estudio, el 90% de los encuestados pertenece al sexo femenino, como se ha encontrado en diferentes estudios (5,17,23,24,26,27,30,31,34,35) , desde 1860, cuando Florence Nigthingale direcciona a la enfermería a un nivel de profesión, hasta la actualidad, la función de las enfermeras en las instituciones de salud obedece al estereotipo del género femenino (36) . El estado civil predominante es ser solteros, seguido por estar casado, igual que lo encontrado en Ibagué (30) , pero en Bogotá (31) , Barranquilla (23) y Cartagena (24) esta condición es minoritaria, aunque el estudio realizado en la Orinoquia no encontró relación de la variable estado civil con la ocurrencia del síndrome, sin embargo, este ha sido asociado en un estudio realizado en Grecia (18) .…”
Section: Discussionunclassified
“…This can generate dissatisfaction, especially in primary care services, which are users' gateway to the health system (21) . In addition, the work environment can be a determining factor for the quality of care and patients' outcomes (30) . The critical point in this type of problem is that professionals may experience difficulties as part of work routine, often not realizing what is happening before feeling depleted (2) .…”
Section: Discussionmentioning
confidence: 99%